Characterizing Organelles in Live Stem Cells Using Label-Free Optical Diffraction Tomography - Kim, Youngkyu; Kim, Tae-Keun; Shin, Yeonhee; Tak, Eunyoung; Song, Gi-Won; Oh, Yeon-Mok; Kim, Jun Ki; Pack, Chan-Gi (Molecules and cells, 2021)
Label-free optical diffraction tomography (ODT), an imaging technology that does not require fluorescent labeling or other pre-processing, can overcome the limitations of conventional cell imaging technologies, such as fluorescence and electron microscopy. In this study, we used ODT to characterize the cellular organelles of three different stem cells-namely, human liver derived stem cell, human umbilical cord matrix derived mesenchymal stem cell, and human induced pluripotent stem cell-based on their refractive index and volume of organelles. The physical property of each stem cell was compared with that of fibroblast. Based on our findings, the characteristic physical properties of specific stem cells can be quantitatively distinguished based on their refractive index and volume of cellular organelles. Altogether, the method employed herein could aid in the distinction of living stem cells from normal cells without the use of fluorescence or specific biomarkers.